Low symmetry metallophthalocyanines and their nanoparticle conjugates for photodynamic antimicrobial chemotherapy - Masilela, Nkosiphile (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
This thesis reports on the syntheses of novel low symmetrically substituted Zn, Sn, Ge and Ti MPc complexes containing a single carboxylic or cysteinyl group available for attachments to MNPs. The complexes were extensively characterized by various techniques to ensure their purity. Various metallic nanoparticles consisting of silver (AgNPs), gold (AuNPs) as well as quantum dots (QDs) were successfully prepared and conjugated to the low symmetry phthalocyanine complexes. The conjugates were successfully characterized using many techniques. The Q-band maxima of the MPcs were observed at completely different wavelength regions depending on the nature of the substituents and the central metal used. Blue shifting of the Q band in the absorption spectra was observed for the complexes in the presence of AuNPs, while aggregation was observed in the presence of quantum dots. The complexes were successfully electrospun into polymer fibers for the antimicrobial inhibition of bacteria. The photophysical and photochemical properties of these complexes were extensively investigated. Higher triplet and singlet oxygen quantum yields were achieved for the Ge Pc complexes, with all the complexes giving reasonable singlet oxygen quantum yields. An enhancement in triplet and singlet oxygen quantum yields was observed for all the complexes in the presence of metal nanoparticles. However, the singlet oxygen quantum yields decreased for all the complexes when incorporated into electrospun fibers. The antimicrobial behaviour of the complexes was investigated against Bacillus Subtilis and Staphylococcus Aureus in solution and in the fiber matrix. High antimicrobial inhibitions were observed for the Ge complexes followed by the ZnPc derivatives. All the low symmetry ZnPc derivatives were conjugated to AgNPs and their antimicrobial behaviour was compared to their symmetrical counterparts. The best antimicrobial inhibition behaviour was observed for the low symmetry Pcs when compared to their symmetrical counterparts. In the absence and in the presence of AgNPs, axially ligated SiPc also showed better antimicrobial activity when it was compared to the unsubstituted ZnPc complex.
Keywords: Nanoparticles; Anti-infective agents; Chemotherapy; Photochemotherapy; Quantum dots; Gold Silver; Phthalocyanines